2016
DOI: 10.1016/j.surg.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in 5-Fluorouracil–related enzymes predict pathologic response after neoadjuvant chemoradiation for rectal cancer

Abstract: Background Patients with rectal cancer undergo preoperative neoadjuvant chemoradiation with approximately 70% exhibiting pathologic down-staging in response to treatment. There is currently no accurate test to predict patients who are likely to be complete responders to therapy. 5-Fluorouracil (5-FU) is regularly used in the neoadjuvant treatment of rectal cancer. Genetic polymorphisms affect the activity of thymidylate synthase (TS), an enzyme involved in 5-FU metabolism. This may account for observed differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Nikas et al indicated in 108 rectal cancer patients that homozygous C/C genotype in MTHFR gene (rs1801133) were 2.91 times more likely to respond to nCRT ( p = 0.015) and 3.25 times more likely not to have recurrence ( p = 0.008) than either the heterozygous C/T or homozygous T/T genotype [132], which is consistent with previous study [133]. Nelson et al investigated SNP located in the promoter region of the TS gene, which potentially affect the enzymatic activity and catabolism of 5-FU, in 50 rectal cancer patients and found that patients with at least one thymidylate synthase 3G allele were more likely to have a complete or partial pathologic response to nCRT containing 5-FU, with odds ratio of 10.4 (95% CI = 1.3–81.6, p = 0.01), than those without [134]. In addition, xeroderma pigmentosum group G ( XPG ) C46T rs1047768 and mutS homolog 6 ( MSH6 ) rs3136228 have been significantly associated with response to nCRT in rectal cancer [135,136].…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…Nikas et al indicated in 108 rectal cancer patients that homozygous C/C genotype in MTHFR gene (rs1801133) were 2.91 times more likely to respond to nCRT ( p = 0.015) and 3.25 times more likely not to have recurrence ( p = 0.008) than either the heterozygous C/T or homozygous T/T genotype [132], which is consistent with previous study [133]. Nelson et al investigated SNP located in the promoter region of the TS gene, which potentially affect the enzymatic activity and catabolism of 5-FU, in 50 rectal cancer patients and found that patients with at least one thymidylate synthase 3G allele were more likely to have a complete or partial pathologic response to nCRT containing 5-FU, with odds ratio of 10.4 (95% CI = 1.3–81.6, p = 0.01), than those without [134]. In addition, xeroderma pigmentosum group G ( XPG ) C46T rs1047768 and mutS homolog 6 ( MSH6 ) rs3136228 have been significantly associated with response to nCRT in rectal cancer [135,136].…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…A number of studies have investigated possible roles for polymorphisms in several 1C metabolism genes in cancer, including those in TS, which may affect CRC susceptibility, disease progression, and TS-targeted chemotherapy [14][15][16][17][18]. Among these are two well-studied TS polymorphisms: (1) TS enhancer region (TSER) 2R/3R and (2) TS 1494del6 [19][20][21].…”
Section: Introductionmentioning
confidence: 99%